2018
DOI: 10.1007/s10067-018-4075-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between the Mediterranean diet and magnetic resonance parameters for knee osteoarthritis: data from the Osteoarthritis Initiative

Abstract: The Mediterranean diet appears to be beneficial for osteoarthritis (OA), but the few data available regarding the association between the diet and the condition are limited to X-ray and clinical findings. The current study aimed to investigate the association between adherence to the Mediterranean diet and knee cartilage morphology, assessed using magnetic resonance (MRI) in a cohort of North American participants. Seven hundred eighty-three participants in the Osteoarthritis Initiative (59.8% females; mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…OA progression is significantly related to oxidative stress and ROS [36], suggesting that adequate intake and/or supplementation of Mg can reduce inflammation and oxidative stress, leading to better preservation of knee structures. Third, Mg is particularly present in the Mediterranean diet, rich in vegetables, and, consequently, this can further justify our findings [22,37,38]. Finally, it is widely known that Mg is able to potentiate the effects of vitamin D on the skeletal system, further reinforcing the positive effect of Mg on knee OA [27].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…OA progression is significantly related to oxidative stress and ROS [36], suggesting that adequate intake and/or supplementation of Mg can reduce inflammation and oxidative stress, leading to better preservation of knee structures. Third, Mg is particularly present in the Mediterranean diet, rich in vegetables, and, consequently, this can further justify our findings [22,37,38]. Finally, it is widely known that Mg is able to potentiate the effects of vitamin D on the skeletal system, further reinforcing the positive effect of Mg on knee OA [27].…”
Section: Discussionsupporting
confidence: 76%
“…We identified several potential confounders in our analyses: body mass index (BMI), physical activity level, assessed with the Physical Activity Scale for the Elderly (PASE) [20], race, smoking habit, educational level, yearly income (< or > $50,000 and missing data), self-reported comorbidities, assessed using the modified Charlson comorbidity score [21], use of analgesic drugs (both topical and systemic) for the management of pain-related knee OA, number of alcoholic drinks consumed in a typical week in the previous 12 months, and adherence to the Mediterranean diet (aMED) [22,23,24,25].…”
Section: Methodsmentioning
confidence: 99%
“…In the Osteoarthritis Initiative, we have already reported that higher aMED scores were not only associated with a significant lower prevalence of knee OA (also after accounting for potential confounders) [12], but also with a better architecture of the knee, investigated through a magnetic resonance investigation. [11] However these data were cross-sectional limiting the interpretation of these findings. With the current research, we have further reinforced the concept that Mediterranean diet could be useful for the prevention of pain in knee OA and for the symptomatic forms through a longitudinal design.…”
Section: Discussionmentioning
confidence: 92%
“…[9,10] Despite this, to the best of our knowledge, only a few cross-sectional studies have studied the association between higher adherence to Mediterranean diet and knee OA, showing overall that people following more strictly Mediterranean diets have a significantly lower likelihood of knee OA and a better knee structure. [11,12] The Mediterranean diet is rich in vitamins and minerals, particularly those derived from vegetables and fruits, whole-meal cereals, nuts, virgin olive oil and fish, which made the risk of deficient micronutrient intakes quite infrequent. This explains why Mediterranean diet is particularly rich in antioxidant vitamins (vitamins E and C) and carotenes were also high.…”
Section: Introductionmentioning
confidence: 99%
“…We identified numerous potential confounders that may influence the relationship between dietary vitamin K and depressive symptoms, including: body mass index (BMI), as measured by a trained nurse; total energy intake (in Kcal); physical activity evaluated using the Physical Activity Scale for the Elderly (PASE) [17]; ethnicity; smoking habits, educational level and yearly income (< or ≥$50,000 or missing data); self-reported comorbidities that were assessed using the modified Charlson comorbidity score [18]; and, adherence to Mediterranean diet according to the score that was suggested by Panagiotakos et al [19] and already reported in the OAI [14,20,21,22]. Data regarding diet, physical activity, demographics and comorbidities were recorded through questionnaires given to the participants.…”
Section: Methodsmentioning
confidence: 99%